PENGARUH PENERAPAN CHSE TERHADAP TINGKAT HUNIAN KAMAR DI NIKITA HOTEL BUKITTINGGI - Vina Kumala; Wina Asty; Pegi Akma Putri (Ensiklopedia of Journal, 2022)
The application of CHSE is one of the strategies to gain the trust of domestic and foreign tourists who will visit during the New Normal period. This study aims to determine how the application of CHSE at Nikita Hotel Bukittinggi and to determine the effect of implementing CHSE on the occupancy rate at Nikita Hotel Bukittinggi. The method used is Associative Quantitative. The sample in this study were guests who had stayed or who were staying at Nikita Hotel Bukittinggi as many as 100 respondents. The sampling technique used was probability sampling and simple random sampling. The technique of data collection is by distributing structured questionnaires. The results of this study show that it has a partial effect on increasing room occupancy rates at Nikita Hotel Bukittinggi, the variable that has the most dominant influence on increasing room occupancy rates at Nikita Hotel Bukittinggi is the cleanliness variable. However, from the results of the OCC formula that the implementation of CHSE does not have much effect on the occupancy rate at Nikita Hotel Bukittinggi because at Nikita Hotel Bukittinggi it has a target of 50% during the new normal but it can be seen in December 2020 which reached 50% occupancy rate from the other 8 months since the implementation CHSE is carried out because of the implementation of PSBB, PPKM, etc. from the government.